Constructing amidoxime-modified porous adsorbents with open architecture for cost-effective and efficient uranium extraction. Issue 18 (27th April 2020) - Li, Zhangnan; Meng, Qinghao; Yang, Yajie; Zou, Xiaoqin; Yuan, Ye; Zhu, Guangshan
Abstract : The dense structure of polymeric matrices exposes only 10–20% of adsorption (amidoxime) groups, thus detracting from the extraction efficiency of uranium from seawater. Abstract : The dense structure of polymeric matrices exposes only 10–20% of adsorption (amidoxime) groups, thus detracting from the extraction efficiency of uranium from seawater. Herein, the amidoxime-modified building units were cross-linked via the Scholl reaction into porous aromatic frameworks (PAFs). Due to the formation of open architecture, PAF adsorbents reveal a larger utilization ratio (>60%) of amidoxime groups. Consequently, PAF samples enable an ultrahigh uranium capacity of 702 mg g −1, which creates a 16-fold capacity enhancement and gains a 7-fold adsorption rate improvement compared with polymer-based adsorbents. Notably, PAF solids are able to be integrated into various devices, thus realizing versatile and efficacious uranium extraction from real seawater (meeting the commercial standard ∼6 mg g −1 in 21 days). In addition, the final cost using our PAF-based adsorbent is US $189.77 per kg uranium, it is in accordance with the prevailing market cost ($100–335 per kg).